Development of a chitosan polymer based composite haemostatic agent and a method for evaluation of performance - Chornyi, Oleksandr; Fedorenko, Volodymyr; Yaremenko, Volodymyr; Ishchenko, Olena; Gureyeva, Svitlana (Technologies and Engineering, 2025)
The aim of this study was to develop an in vitro method for evaluating the hemostatic efficacy of composites and to investigate the factors influencing the hemostatic efficacy of polymer composite materials based on chitosan using the developed method. Existing contact haemostatic composite materials based on zeolites and chitosan polymer were reviewed. For research and quality control work with haemostatics, it was required to test their haemostatic performance. Conducting in vivo studies required intervention in a living organism and is undesirable for ethical reasons. A generally accepted system for assessing the efficacy of hemostatic agents in vitro does not exist. A methodology for analyses to determine the haemostatic properties of composites has been developed. The main quality attributes of haemostatics, such as gel formation time and permeability, were determined. The composition and method for producing the finished haemostatic composite material were developed. The composite contains a salt of chitosan and lactic acid, polyethylene glycol 4,000. The effect of carboxylic acids and surfactants on the properties of the composite was studied. Chitosan with a molecular weight of at least 80,000 Dalton and a degree of deacetylation of 85-95% was selected. The “active” and “inactive” forms of chitosan, which affect the haemostatic properties of the composite, were studied. The process for obtaining the “active” form of chitosan from the “inactive” form by redeposition, which consists in the interaction of chitosan with carboxylic acid to obtain a soluble salt and subsequent alkali precipitation, was developed. The influence of the following factors on the properties of the resulting product was studied: solvent in the salt synthesis reaction; molar ratio of lactic acid and chitosan; particle size of the haemostatic powder. The resulting haemostatic is effective in binding water and blood into a fixed gel-like clot. The product has sufficient permeability and haemostatic performance. The clot formed by binding liquids is stable for 24 hours